Evaluation of Immunohistochemical Findings and Clinical Features associated with Local Aggressiveness in Basal Cell Carcinoma - Simin Shamsi meymandi; Shahriar Dabiri; Alireza ZeynadiniMeymand; Maryam Iranpour; Maryam Khalili; Sorour Alijani; Mahin Aflatoonian (Iranian Society of Pathology, 2019)
Background & Objective:Basal cell carcinoma (BCC) is classified into BCC1 or low risk (nodular, superficial type) and BCC2 or high risk (micronodular, morpheaform, infiltrative, and basosquamous types) based on clinical behavior. This study attempts to evaluate immunohistochemical (IHC) findings and clinical features associated with local aggressiveness and recurrence in BCC lesions.Methods:This is a cross-sectional descriptive study conducted on 42 paraffin blocks (22 BCC1, 20 in BCC2) at Pathology Department of Afzalipour Teaching Hospital. First, demographic features of the patients were recorded and pathology blocks were classified by two dermatopathologists based on histopathological types of BCC1 and BCC2. Then, primary monoclonal antibodies including CD10, CD1a, SMA, Ki67, CD34, and P53 were utilized for IHC study. We compared BCC1 and BCC2 according to IHC markers, demographic features of patients, and tumoral features.Results:The mean number of Langerhans cells (LCs) within epidermis above tumor mass was 14+1.92 and 4.7±1.23 in BCC1 and BCC2, respectively; these results show a significant difference between the two groups (P=0.001). P53 was positive in 41.13±6.39% and 74.5 ±6.26% of the tumor cells in BCC1 and BCC2 groups, which was statistically significant (P=0.001). Also, the mean number of blood vessels was 14.40±1.30 and 21.40±1.97 in BCC1 and BCC2, that was statistically significant (P=0.005).Conclusion: Higher numbers of angiogenesis (SMA positive) and positive P53 were observed in BCC2 than BCC1. Also, more active positive CD1a cells were observed in BCC1 compared to BCC2.